Advanced ceramic materials for electrolytes and electrodes in reversible solid oxide cells - Panagiotis Kopras; Constantinos Tsanaktsidis; Nikolas Kiratzis (Academia Green Energy)
Manmade climate change caused by the burning of fossil fuels has created the need for an energy transition to renewable energy sources. Reversible solid oxide cell (rSOC) technologies can play an important role in this transition, as they offer the potential to produce and store energy on demand. Current challenges are associated with cost, durability, material stability, and low round-trip efficiency. These challenges can be addressed through the prudent selection and fabrication of ceramic cell materials. After decades of research, a lot of significant achievements and progress have been made in addressing the major challenges, including lowering the operating temperatures to <500°C, mass-producing cells with high uniform quality that exhibit high initial performance and low degradation rates, and developing fuel electrodes with high resistance to carbon deposition and tolerance to material and fuel impurities. According to the composition and requirements of each component of an rSOC, this review summarizes the research progress based on ceramic materials and discusses the merits and demerits of current cell materials, along with necessary fabrication approaches in order to achieve suitable electrochemical performance in line with these advancements.